Synthesis and photochemical reactions of 6-alkenyl-3-phenylcyclohex-2-enones - Bradley, Stephen Anthony (Trinity College (Dublin, Ireland). School of Chemistry, 2002)
The synthesis and photochemical reactions of a series of molecules containing both the 3-phenylcylohexenone moiety and an C-6 substituted alkenyl side chain (2- propenyl, 3-butenyl and 4-pentenyl) are described. The C-6 position was further substituted with a carbomethoxy group to generate a conformational control factor.A synthetic strategy involving a three-step sequence was employed. This involved alkylation of a β-ketoester with a halogenated substituent, followed by Michael addition, with phenyl vinyl ketone prior to ring closure to the cyclohexenone. Cyclohexenone derivatives containing a pyrimidine ring were also investigated. In this case results suggested a thermodynamically controlled reaction with pka dependency in the Michael addition step.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin